2001
DOI: 10.4049/jimmunol.166.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Immune Privilege Promoted by the Presentation of Peptide on Tolerogenic B Cells in the Spleen. II. Evidence for Presentation by Qa-1

Abstract: Ocular immune privilege is the result of several unique features of the eye, including the systemic down-regulation of Th1 immune responses to Ags encountered in the anterior chamber of the eye—a phenomenon termed anterior chamber-associated immune deviation (ACAID). The induction of ACAID requires the participation of three cell populations: the ocular ACAID APC, the splenic B cell, and the splenic T cell. Because B cells have been implicated in tolerogenic Ag presentation in other systems, we hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 34 publications
3
68
0
Order By: Relevance
“…The presence of such a regulatory mechanism is supported by a recent finding that both impairment of B cell activation and decrease in CD8 ϩ T cells is associated with the exacerbation of chronic intestinal inflammation observed in G␣i2 KO mice (89). Furthermore, B cells have been shown to induce such Tregs in a ␤ 2 -microglobulin-dependent fashion at the ocular immune privilege site (90). Therefore, Bregs directly or indirectly interact with several immune cell subsets to control immune responses.…”
Section: Mechanisms Other Than Cytokine Production By Which B Cells Csupporting
confidence: 48%
“…The presence of such a regulatory mechanism is supported by a recent finding that both impairment of B cell activation and decrease in CD8 ϩ T cells is associated with the exacerbation of chronic intestinal inflammation observed in G␣i2 KO mice (89). Furthermore, B cells have been shown to induce such Tregs in a ␤ 2 -microglobulin-dependent fashion at the ocular immune privilege site (90). Therefore, Bregs directly or indirectly interact with several immune cell subsets to control immune responses.…”
Section: Mechanisms Other Than Cytokine Production By Which B Cells Csupporting
confidence: 48%
“…A combination of in vitro and in vivo studies has shown that the induction of ACAID begins when F4/ 80 ϩ ocular APCs migrate to the spleen where they release Ag, which is captured and processed by splenic B cells (15,16). These studies also demonstrated that antigenic moieties are released from F4/80 ϩ ocular APCs and captured via the BCR on the splenic B cells, internalized, and processed in acidified lysosomes before being presented to T cells (16).…”
mentioning
confidence: 82%
“…One candidate regulatory subset is the CD8 ϩ T cell population recognizing the invariant MHC class I molecule Qa-1 (HLA-E in human), which is expressed at high levels on certain B cell subpopulations. Qa-1 recognition may include mCD94͞ NKG2A (40) and induces negative regulatory activity in experimental autoimmune encephalomyelitis, oral tolerance, and B cell-dependent ocular tolerance (14,21,41). Another candidate is intestinal CD4 ϩ CD8␣ ϩ DP T cells, because they were expanded during B cell-mediated protection.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models of oral tolerance, B cells are important for maintenance of a protective cytokine microenvironment in gut-associated lymphoid tissue (13). Similarly, B cells were also required for efficient induction of antigen-specific T cell unresponsiveness in the ocular anterior chamber (14,15) and in the lung in the context of respiratory allergen (16). B cells also attenuate immune responses in certain autoimmune models.…”
mentioning
confidence: 99%
See 1 more Smart Citation